1988
DOI: 10.2514/3.9852
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed CO2 laser-induced effects on water droplets

Abstract: Pulsed high-power CO 2 laser beams propagating through the atmosphere can be affected by such different linear or nonlinear phenomena as aerosol and molecular absorption, scattering, turbulence, thermal blooming, or optical breakdown, depending on the atmospheric characteristics and laser parameters. An experimental investigation was carried out to study the pulsed CO 2 laser-induced effects on water droplets. Water droplets with radii of 8-400 /im were irradiated. The average fluences used for the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This optical breakdown results in the formation of plasma (Autric et al, 1988) that absorbs much of the incident laser radiation. The motion of the drop takes place nearly diametrically opposite to this hot spot or spark for transparent and near transparent drops due to the thermal gradient that the hot spot generates.…”
Section: Direction Of Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…This optical breakdown results in the formation of plasma (Autric et al, 1988) that absorbs much of the incident laser radiation. The motion of the drop takes place nearly diametrically opposite to this hot spot or spark for transparent and near transparent drops due to the thermal gradient that the hot spot generates.…”
Section: Direction Of Motionmentioning
confidence: 99%
“…In USA too, the explosion of water drops under laser was studied (Singh and Knight, 1978;(Carls and Brock, 1987), so was the process of droplet heating under a continuous laser beam (Park and Armstrong, 1989) and also the hydrodynamics of a drop when exposed to pulsed laser (Zardecki and Pendleton, 1989). (Autric et al, 1988) also reported their findings on the effects of pulsed CO 2 on water droplets. The focus of the study of atmospheric laser propagation has also included cloud science, particularly cloud-clearing using high-energy laser beams and new applications such as wireless communication using laser beams.…”
Section: Introductionmentioning
confidence: 99%